The Courtyard of My House: an Analysis of the Benefits of Group Intervention for Women in Homelessness from a Professional Perspective - Díaz González, José Manuel; Hernández Martín, Jennifer; Fustier García, Nuria; Matulic Domandzic, María Virginia (Cuadernos de Trabajo Social, 2025)
Female homelessness is a complex and often invisible phenomenon, influenced by structural inequalities and the lack of a gender perspective in public policies, highlighting the need for tailored approaches for their social integration. This study explores group intervention as a strategy for the social integration of women experiencing homelessness, focusing on the initiative "El Patio de mi Casa." The objective is to understand social work professionals’ perceptions of the impact of this intervention on women, identifying its benefits and key aspects for implementation. A qualitative methodology was employed, using structured interviews with ten professionals collaborating directly with homeless women in Santa Cruz de Tenerife. The results show that group intervention facilitates socialization, empowerment, and the improvement of participants’ emotional and physical well-being. The professionals recommend the permanent adoption of this initiative, indicating the need for methodological and logistical adaptations to optimize its impact. It is concluded that "El Patio de mi Casa" is an effective tool in promoting empowerment and social inclusion of homeless women, although its implementation requires a participatory approach and long-term commitment. Furthermore, the gap between theory and practice underscores the need to strengthen training in group interventions, ensuring that professionals are equipped to effectively address the complex needs of this group and promote sustainable social inclusion and recovery.